PROBLEMATIKA PERLINDUNGAN PEKERJA MIGRAN INDONESIA NONPROSEDURAL YANG BEKERJA DI LUAR NEGERI - Erwin, Rahmi (Ensiklopedia Research and Community Service Review, 2025)
Abstract: Indonesia is one of the countries that provides a large contribution to the workforce, with the high interest of Indonesian migrant workers to work abroad, this creates various problems and problems related to guarantees of their human rights and guaranteed protection of work and safety, these migrant workers can be categorized into Procedural Migrant Workers and Non-Procedural Migrant Workers, in various cases of violations, Non-Procedural Migrant Workers are often denied their basic rights and have difficulty getting guaranteed protection because their departure is not equipped with the appropriate document requirements and is not registered with immigration, this has given rise to increasingly polemics. high number of complaints and reports of migrant workers abroad. This research uses the approach method used in this writing, namely approach juridical normative as the main approach to existing laws and regulations. The data used is secondary data and primary data, and is analyzed sequentially qualitative and presented in form descriptive. Protection of Migrant Workers has become the Government's obligation, thus the government must have a guidance, supervision and protection mechanism so that migrant workers obtain security for their jobs. The role of various units that involve cross-sectoral sectors must be optimized and integrated to minimize the potential for violations of the rights of Indonesian Migrant Workers.Keywords: Protection, Indonesian Migrant Workers, Non-Procedural Indonesian Migrant Workers